Analysis of the Contents of the Cleanliness Campaign in the Kompas TV article “Blitar Police Car Turned into a Mask Waste Bank” - Sari, Yoana Puspita; Savitri, Hikmawati Fadjri Devi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The The COVID-19 pandemic requires people to comply with health protocols, one of whichis wearing a mask. The use of masks is part of a comprehensive series of prevention andcontrol measures that can limit the spread of the virus. The increasing amount of maskwaste and the absence of waste management have a negative impact on environmentalhygiene and health. Seeing this case, it is necessary to carry out a mask waste managementcampaign. The purpose of this study was to analyze the contents of the hygiene campaignin the Kompas TV article